Reduction of diameter of the left ventricle of dogs by plication of the left ventricular free wall - De Andrade, James Newton Bizetto Meira [UNESP]; Wouk, Antonio Felipe; Camacho, Aparecido Antonio [UNESP]; Branco Germiniani, Clotilde de Lourdes; Gavazzoni, Lilian (American Veterinary Medical Association (AVMA), 2001)
Objective - To determine effects of reducing the diameter of the left ventricle of dogs by plication of the left ventricular free wall. Animals - 8 healthy adult mixed-breed dogs. Procedure - Left lateral thoracotomy and a T-shaped pericardiotomy were performed. The free wall of the left ventricle was imbricated with 3 interrupted transfixing sutures applied in a horizontal mattress pattern, using 3-0 polypropylene suture assembled on a straight cutting needle. Surgeons were careful to avoid the coronary vessels. Echocardiography was performed 24 hours before and 48 hours after surgery. Electrocardiography was performed before and 1, 2, 7, 15, 21, 30, and 60 days after surgery. Results - Echocardiographic measurements revealed that the diameter of the left ventricle was reduced by a mean of 23.5%. Electrocardiography revealed ventricular premature complexes 24 hours after surgery that regressed without treatment during the first week after surgery. Conclusions and Clinical Relevance - Plication of the left ventricular free wall of dogs can reduce end-diastolic and end-systolic dimensions of the left ventricle. The technique is simple and does not require cardiopulmonary bypass. According to Laplace's law, the reduction of cardiac diameter leads to reduction on free-wall tension and may improve left ventricular function in dilatated hearts. Thus, additional studies involving dogs with dilated cardiomyopathy should be conducted.
Keywords: animal; animal disease; congestive cardiomyopathy; dog; dog disease; Doppler echocardiography; electrocardiography; female; heart surgery; heart ventricle; histology; male; methodology; pericardiectomy; Animals; Cardiac Surgical Procedures; Cardiomyopathy, Dilated; Dog Diseases; Dogs; Echocardiography, Doppler, Color; Electrocardiography; Female; Heart Ventricles; Male; Pericardiectomy